Polemic Discourse on the Zoning Education System Policy by the Ministry of Education and Culture in Bondowoso Indonesia - Widya Oryzani (RIRAI Publisher, 2023)
This study aims to describe the polemic over the zoning education system policy in the Bondowoso region. The method used is qualitative research with the type of critical discourse analysis research and the Fairclough critical discourse analysis model. The data in this study are in the form of words, phrases, clauses, and sentences related to the text and the results of the interviews which show polemics. Sources of data for this research were taken from Ministry of Education and Culture Regulations, follow-up policies from the Education Office, interview results, and online media documentation. The instruments used in data collection were the researchers themselves who acted as key instruments, devices, recording devices, note sheets, and laptops. Data collection techniques in this study were carried out using documentation, interviews and observation techniques. Data analysis techniques, researchers used critical discourse analysis developed by Fairclough by way of description, interpretation and explanation. The results of the study show the use of lingual features such as lexical processes, euphemisms, transitivity, and modality, as well as the ideology of each group involved. The polemic found from each group with the existence of a zoning education system policy can be used as literacy material and also for consideration in making further policies.